2021
DOI: 10.7759/cureus.14777
|View full text |Cite
|
Sign up to set email alerts
|

Response of Helicobacter Pylori Eradication Treatment in Patients With Normal and Below-Normal Serum Vitamin D Levels

Abstract: The infection of Helicobacter pylori (H. pylori) is affected by the host immune system and the genetic makeup. It is postulated that deficiency of vitamin D may interfere in normal immunological response to infectious agents, including H. pylori, and increase the risk of infection. This study aims to find the relationship between vitamin D status in the body and patient's response to H. pylori eradication treatment. MethodsOne hundred and fifty patients (n = 150) between the ages of 18 and 60 years of either g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This theory was tested using a classical clarithromycin-based triple eradication therapy of 14 days duration [ 20 ]. Magsi et al also reported an even higher, ascending discrepancy in vitamin D levels between H. pylori infected patients that responded to the same therapeutic regimen and those who did not [ 46 ]. Similar findings were reported by Almani et al in their study, in which the identical, classical therapeutic scheme failed to eradicate H. pylori infection in more than 80% of patients with vitamin D levels below 30 ng/mL [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…This theory was tested using a classical clarithromycin-based triple eradication therapy of 14 days duration [ 20 ]. Magsi et al also reported an even higher, ascending discrepancy in vitamin D levels between H. pylori infected patients that responded to the same therapeutic regimen and those who did not [ 46 ]. Similar findings were reported by Almani et al in their study, in which the identical, classical therapeutic scheme failed to eradicate H. pylori infection in more than 80% of patients with vitamin D levels below 30 ng/mL [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The effects of H. pylori eradication on serum vitamin levels have aroused extensive interest. Several studies ( 2 , 57 59 ) found that patients that underwent successful H. pylori eradication had higher serum vitamin D levels than patients with in which eradication failed. Several studies ( 13 , 14 , 60 , 61 ) described vitamin B 12 level discrepancies before and after successful H. pylori eradication therapy; nevertheless, there were also inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori ( H. pylori ) is a gastric gram-negative, spiral-shaped microaerophilic pathogen ( 1 ). About half of the global population is infected with H. pylori , and the infection rate in developing countries is higher than in developed countries ( 2 , 3 ). H. pylori is the main risk for chronic gastritis, gastric ulcer, gastric cancer and mucosa-associated lymphoid tissue–associated lymphoma ( 4 – 6 ).…”
Section: Introductionmentioning
confidence: 99%